Consensus Recommendations for Blood Culture Use in Critically Ill Children Using a Modified Delphi Approach*. Issue 9 (September 2021) - Woods-Hill, Charlotte Z.; Koontz, Danielle W.; Voskertchian, Annie; Xie, Anping; Shea, Judy; Miller, Marlene R.; Fackler, James C.; Milstone, Aaron M.
Abstract : Objectives: Blood cultures are fundamental in evaluating for sepsis, but excessive cultures can lead to false-positive results and unnecessary antibiotics. Our objective was to create consensus recommendations focusing on when to safely avoid blood cultures in PICU patients. Design: A panel of 29 multidisciplinary experts engaged in a two-part modified Delphi process. Round 1 consisted of a literature summary and an electronic survey sent to invited participants. In the survey, participants rated a series of recommendations about when to avoid blood cultures on five-point Likert scale. Consensus was achieved for the recommendation(s) if 75% of respondents chose a score of 4 or 5, and these were included in the final recommendations. Any recommendations that did not meet these a priori criteria for consensus were discussed during the in-person expert panel review (Round 2). Round 2 was facilitated by an independent expert in consensus methodology. After a review of the survey results, comments from round 1, and group discussion, the panelists voted on these recommendations in real-time. Setting: Experts' institutions; in-person discussion in Baltimore, MD. Subjects: Experts in pediatric critical care, infectious diseases, nephrology, oncology, and laboratory medicine. Interventions: None. Measurements and Main Results: Of the 27 original recommendations, 18 met criteria for achieving consensus in Round 1; some were modified for clarity or condensed from multiple into single recommendations during Round 2. The remaining nine recommendations were discussed and modified until consensus was achieved during Round 2, which had 26 real-time voting participants. The final document contains 19 recommendations. Conclusions: Using a modified Delphi process, we created consensus recommendations on when to avoid blood cultures and prevent overuse in the PICU. These recommendations are a critical step in disseminating diagnostic stewardship on a wider scale in critically ill children.